THE EFFECT OF MOTIVATION AND ONLINE LEARNING ON TEACHER PERFORMANCE AT DARUL HIKMAH IT HIGH SCHOOL DURING THE COVID-19 PANDEMIC. - H. Lukman Achmad; Erwin Erwin; Eka Sutisna (JOEL: Journal of Educational and Language Research, 2022)
This research was conducted to determine the motivation and online learning process in SMA IT Darul Hikmah on teacher performance. The research method used in this study is multiple regression analysis to determine the effect of providing motivation and online learning on teacher performance. The results showed that simultaneously there was a significant positive effect between the variables of Work Motivation (X1) and Online Learning (X2) on Teacher Performance (Y), where F arithmetic > F table that was 7.993 > 3.37 and a significance of 0.000 < 0.05 then Ho is rejected and Ha is accepted. Judging from the value of the multiple correlation coefficient, R = .549, it means that the influence of Work Motivation and Online Learning on Teacher Performance is 0.549, which means that it has a strong, unidirectional, and positive influence. So the simultaneous test (F test) and the results of multiple correlation analysis, namely R, can be concluded that the variables of Work Motivation (X1) and Online Learning (X2) have a simultaneous positive and significant effect on Teacher Performance (Y). Then can the result of the magnitude of the contribution value of the influence of X1 and X2 on Y, namely: KD = 0.302. This means that the independent variable can explain the variation of the dependent variable by 30.2%, while the remaining 69.8% is explained by other factors.